Liquidus Temperature Measurements for Metallurgical Slags - Grimsey, Eric; Yan, X.Y.; Li, N. (GK Williams CRC, Melbourne, 1996)
A technique is being developed for the fast measurement of the liquidus temperature of synthetic and industrial slags. The technique involves using a type K thermocouple centred within a nickel cylinder to record the heating profile after immersion of the cylinder into a molten bath. Upon immersion of the cold cylinder into the bath, a layer of slag freezes onto the surface. When this melts away, the rate of heating of the cylinder increases, and the point of this increase provides an estimate of the liquidus temperature of the slag. The temperature data are logged and analysed using a PC-based system, to detect this point The technique is illustrated here for iron saturated fayalite slags with various additions of lime and magnesia, as well as for industrial smelting slags.